The daily relations between workplace anger, coping strategies, work outcomes, and workplace affiliation - Umbra, Robin; Fasbender, Ulrike (Frontiers in Psychology, 2025)
This study examines the daily relations among workplace anger, coping strategies, work outcomes, and employee dispositions using a conceptual framework based on affective events theory and cognitive perspectives on emotions. A sample of 214 full-time employees took part in a two-week study, contributing 1,611 daily observations through an experience sampling approach. Contrary to the assumption that workplace anger always detrimentally relates to work outcomes, the results showed a nonsignificant relation between workplace anger and workplace resource depletion, as well as a positive link between workplace anger and goal achievement. These relations were dependent on the coping strategies used by employees in response to anger-inducing situations, as well as their attitudes toward workplace affiliation. These findings suggest the need to expand affective events theory to include coping strategies as a mediator between affective responses and work outcomes. They also highlight the importance of integrating employee-level factors into organizational research models.